Corticosteroids, but not NSAIDs, are associated with less Alzheimer neuropathology - Beeri, Michal Schnaider (2011)
OBJECTIVE: To test the hypothesis that corticosteroid and non-steroidal anti-inflammatory (NSAIDs) medications are associated with less global and regional Alzheimer’s disease (AD) neuropathology. METHODS: This postmortem study was based on 694 brains of subjects from the Mount Sinai School of Medicine Brain Bank who did not have neuropathologies other than neuritic plaques (NPs), neurofibrillary tangles (NFTs), or cerebrovascular disease. Densities of NPs and of NFTs were assessed in several neocortical regions and in the hippocampus, entorhinal cortex, and amygdala. Counts of NPs in several neocortical regions were also assessed. For each neuropathology measure, analyses of covariance controlling for age at death and sex compared subjects who received only corticosteroids (n=54) or those who received only NSAIDs (n=56) to the same comparison group, subjects who received neither (n=576). RESULTS: Subjects receiving corticosteroids had significantly lower ratings and counts of NPs for all neuropathological measures, and NFTs overall and in the cerebral cortex and amygdala. In contrast, no measures were significant for subjects who received NSAIDs. CONCLUSIONS: Use of corticosteroids was associated with approximately 50% less NPs and NFTs in most brain regions examined, compared to non-medicated subjects. In contrast, use of NSAIDs was not substantially associated with the reductions in hallmark lesions of AD. Since corticosteroids have anti-inflammatory as well as a myriad of other neurobiological effects, more direct studies in model systems could reveal novel therapeutic targets and mechanisms for AD lesion reduction.